Intracurricular Learning of Arabic Language Education in Building Religious Values - Satrio (Indra institute Research & Publication, 2024)
This research aims to explore the formation of religious values ​​in intracurricular Arabic language education learning which are implemented in daily attitudes and behavior, both in the school environment and in the Arabic language education learning process. The research method used is the library research method. This method explores data from written materials, namely researching books or reading materials that are related to the problem being studied. To obtain the necessary data, researchers collected data using several primary data sources and secondary data sources and by means of documentary studies and literature studies. The research results found that intracurricular learning in Arabic language education in building religious values ​​was carried out in a systematic way using a curriculum that had been determined by the leadership of the educational institution and was in accordance with the elements of learning. The implementation of religious values ​​through intracurricular learning in Arabic language education must receive full support from various parties, because it has become a shared commitment and responsibility. Then what Arabic language education teachers do in building students' religious values ​​is by getting into the habit of practicing what is the goal of learning Arabic. This is in accordance with the statement that learning must be oriented towards active, creative, effective and fun learning.